Another proof of wiener's short secret exponent - Asbullah, Muhammad Asyraf; Kamel Ariffin, Muhammad Rezal (University of Malaya, 2019)
Wiener’s short secret exponent attack is a well-known crypt-analytical result upon the RSA cryptosystem using a Diophantine’s method called continued fractions. We recall that Wiener’s attack works efficiently on RSA with the condition that the secret exponent d<13N14. Later, the upper bound was improved satisfying푑<√6√26푁14. In this work, we present another proof to Wiener’s short secret exponent satisfying푑<12푁14. We remark that our result is slightly better than the previously mentioned attacks.